Examination of Gender-Related Differential Item Functioning Through Poly-BW Indices - Huang, Tsai-Wei; Wu, Pei-Chen; Mok, Magdalena Mo Ching (Frontiers in Psychology, 2022)
Abstract The existing DIF detection approaches relying on item difficulty or item discrimination are limited for understanding the associates of DIF items, and consequently DIF items were conventionally either deleted or ignored. Given the importance of minimizing DIF items in test construction, teachers or testing practitioners need more information regarding possible associates of DIF items. Using an example of a teacher-made mathematics achievement test, this study aimed to examine how the Poly-BW indices (power, defenselessness, disturbance, and hint) contributed to the properties of gender-related DIF items. Data from a 34-item mathematics achievement test involving 1439 seventh-grade students from Taiwan (51.01% boys and 48.99% girls) showed that the differences of the defenselessness (mp) and power (cp) indices between males and females served as salient predictors of the DIF measures estimated by the Poly-SIBTEST procedure and with satisfactory accuracy of hit rates. Items with relatively large defenselessness for males were likely to present male-favoring DIFs, whereas items with relatively large power for males were likely to present female-favoring DIFs. The Poly-BW indices yielded directions for modifying items for teachers in practices.